CRITICAL DISCOURSE ANALYSIS OF PERSUASION AND POWER IN DONALD TRUMP’S INAUGURATION SPEECH 2025 - Fariza, Nurul; Mahyuni Mahyuni; Arafiq Arafiq; Kamaludin Yusra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research examines Donald Trump's 2025 Inauguration Speeches through the lens of critical discourse analysis, analysing persuasion, power and rhetorical strategies. Employing Norman Fairclough's three-dimensional framework, textual analysis, discursive practice, and social practice, the study investigates how Trump constructs persuasion and power dynamic through mobilizing public support. Data were taken from official transcript and video recording of the speech analysed using qualitative methods with descriptive type. The analysis revealed that Donald Trump uses inclusive pronouns, modality, repetition, metaphor, and Aristotelian appeals to ethos, pathos, and logos to build solidarity with his audience and reinforce nationalist rhetoric. A Discursive Practice Analysis revealed the speech has been influenced by political discourse and broadcast to global audiences. The social practice perspective positions the speech within U.S. political traditions and reflecting populist ideology. This approach contributes to the emerging field of political discourse analysis. This field shows that language is more than just a way to communicate, it is also a way to control people and spread ideas.